PyUNIxMD: A Python‐based excited state molecular dynamics package. Issue 24 (1st July 2021) - Lee, In Seong; Ha, Jong‐Kwon; Han, Daeho; Kim, Tae In; Moon, Sung Wook; Min, Seung Kyu
Abstract: Theoretical/computational description of excited state molecular dynamics is nowadays a crucial tool for understanding light‐matter interactions in many materials. Here we present an open‐source Python‐based nonadiabatic molecular dynamics program package, namely PyUNIxMD, to deal with mixed quantum‐classical dynamics for correlated electron‐nuclear propagation. The PyUNIxMD provides many interfaces for quantum chemical calculation methods with commercial and noncommercial ab initio and semiempirical quantum chemistry programs. In addition, the PyUNIxMD offers many nonadiabatic molecular dynamics algorithms such as fewest‐switch surface hopping and its derivatives as well as decoherence‐induced surface hopping based on the exact factorization (DISH‐XF) and coupled‐trajectory mixed quantum‐classical dynamics (CTMQC) for general purposes. Detailed structures and flows of PyUNIxMD are explained for the further implementations by developers. We perform a nonadiabatic molecular dynamics simulation for a molecular motor system as a simple demonstration. Abstract : Python‐based UNIversal Excited state Molecular Dynamics. PyUNIxMD is a Python‐based nonadiabatic molecular dynamics simulation package based on mixed quantum classical frameworks for general purposes. It incorporates various dynamics algorithms and interfaces for popular quantum chemistry softwares. Especially, PyUNIxMD provides novel methodologies such as decoherence‐induced surface hopping dynamics based on exact factorization and coupled‐trajectory mixed quantum classical dynamics to account for quantum decoherence.